Handling of Recording Letters on Disposition Sheets at UPT Food Security, Food Crops and Horticulture Services North Sumatra Province - M. Fahrizal Adrian; Muhammad Irwan Padli Nasution (International Journal of Management Research and Economics, 2024)
This research aims to fulfill the internship task as well as to provide knowledge about recording correspondence or what is often called disposition, but in this research I will explain what I know and what I have learned about the disposition of correspondence in the UPT. North Sumatra Province Food Security and Horticulture Service.